Amplitude of low-frequency fluctuations in childhood-onset schizophrenia with or without obsessive-compulsive symptoms: a resting-state functional magnetic resonance imaging study - Yinghui Liang (Termedia Publishing House, 2018)
Introduction Childhood-onset schizophrenia with obsessive-compulsive symptoms (COSO) and without obsessive-compulsive symptoms (COS) share considerable overlap in clinical features and genetic risk factors. However, the extent of brain functional abnormalities in COSO and COS is poorly understood.